Entrepreneurship in the city: sustainability and green entrepreneurs - Franco, Stefano (TeMA - Journal of Land Use, Mobility and Environment, 2020)
Starting from the relationship between urban planning and mobility management, TeMA has gradually expanded the view of the covered topics, always following a rigorous scientific in-depth analysis. This section of the Journal, Review Notes, is the expression of a continuous updating of emerging topics concerning relationships among urban planning, mobility and environment, through a collection of short scientific papers. The Review Notes are made of four parts. Each section examines a specific aspect of the broader information storage within the main interests of TeMA Journal. In particular, the Economy, business and land use section aims at presenting recent advancements on relevant topics that underlie socio-economic relationships between firms and territories. The present note underlines the benefits that entrepreneurship exerts on the city, with a specific focus on sustainability and green entrepreneurs. These ones are individuals who start business ventures without just seeking their profit maximization as a unique goal, but rather contribute to the sustainable development of the communities in which they are embedded. However, in order for them to have positive and long-lasting impacts, they need to cooperate with networks that embed several stakeholders and mainly local governments.